Unbroken [compact disc, unabridged] : a World War II airman's story of survival, resilience, and redemption - Hillenbrand, Laura (Random House, 2010)
In 1943, while World War II raged on in the Pacific Theater, Lieutenant Louis Zamperini was the only survivor of a deadly plane crash in the middle of the ocean. Zamperini had a troubled youth, yet honed his athletic skills and made it all the way to the 1934 Olympics in Berlin. However, what lay before him was a physical gauntlet unlike anything he had encountered before: thousands of miles of open ocean, a small raft, and no food or water.